Spatial Modelling of Landscape and Land Cover Pattern at Semarang City - Kurniawati Sugiyo; Supriatna Supriatna; Risnarto Risnarto (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
Semarang City is one of the largest city in Indonesia. Tidal flooding at the coast and landslide at the hills, are the issues the city currently dealing with as a side effect of land conversion. The study on spatial pattern and its change of landscape/land cover is important for a better understanding in environmental management at this city. Landsat images from 1996, 2003 and 2016 and landscape indices were used to analyze landscape/land cover pattern and its change. Binary Logistic Regression and GIS were used to build a mathematical and spatial modelling of landscape/land cover change using driving factors. Land cover change mostly happened to shrubs that turned into mixed crops at 1996-2003; while at 2003-2016, it happened to agriculture that turned into settlements. Landscape indices shows that the highest land utilization and land fragmentation with high mixing and diversity mostly occurred at elevation 25-100 MASL at 1996-2003; and at 2003-2016, it occurred at elevation 100-500 MASL. Spatial modeling of landscape/land cover at Semarang City can explain 61,98% from its actual condition. Elevation has the strongest significance relation to the landscape/land cover change.